Implementation of Government Regulation Policies towards the Empowerment of MSMEs - Larasati, Nadia (QISTINA: Jurnal Multidisiplin Indonesia, 2022)
This study aims to determine the implementation of Government Regulation Number 7 of 2021 on the empowerment of MSMEs during the covid-19 pandemic, and to determine the role of MSMEs in supporting empowerment programs from local governments during the covid-19 pandemic. The methods used in this study are qualitative descriptive. Data collection techniques through observation, documentation, questionnaires (Questionaire), and interviews. The subject of this study was (7) seven people, namely the Head of the SME Empowerment Section of the Cooperative, SME, and Industrial Office of Bantul Regency, two Managers of Banguntapan Street Food (BSF), two MSME Actors, and two Banguntapan Subdistrict Communities. Data analysis techniques are carried out by covering interview transcripts, data reduction, data interpretation, data validity examination using triangulation techniques. The results of this study concluded that the strategic role of DKUKMP Bantul Regency in efforts to empower MSMEs during the covid-19 pandemic in order to realize welfare for MSMEs as a form of implementation of Government Regulation of the Republic of Indonesia Number 7 of 2021 is to provide 1) Facilitation of digitalization/information technology 4.0, 2) MSME Training, 3) Facilitation of increased business diversification, 4) Development of MSME Product Promotion 5) Facilitation of Productivity Improvement, and 6) Facilitation of Partnerships. The role of MSMEs in supporting empowerment programs from local governments during the Covid-19 pandemic is as 1) Job opening, 2) Helping to promote and introduce local products, 3) Support the procurement of MSME empowerment training, 4) Improve the national economy , and 5) Sources of innovation.